ANALISIS STRUKTUR, PERILAKU DAN KINERJA PASAR KARET DI KECAMATAN PANGKALAN KURAS DAN KECAMATAN BUNUT KABUPATEN PELALAWAN - Yusriwandi Yusriwandi; Novia Dewi; Shorea Khaswarina (UIR Press, 2016)
The research was conducted at October 2015 – Maret 2016 in Pangkalan Kuras and Bunut district, Pelalawan regency. The marketing purpose is PT. Bangkinang. The purpose of the research was to know marketing path, market structure, market conduct, and market performance. Market structure approach are using market share analysis, Concentration Rasio, and Barrier to Entry. Market conduct approach is using descriptif qualitatif analysis about the market that become research object. While market performance approach is using marketing margins analysis in this case based on the concept of the product reference. Respondent in this research was rubber farmer with respondent totatlly 36, and sales with 7 respondent people. This research used survey method. The result of this research showed that structure of rubber market in Pangkalan Kuras and Bunut district, Pelalawan regency direct at monopolystic market. Conduct of rubber market occur at not perfect market competition. The matter can refer to out of result correlation analysis and elasticity price transmission with market structure which shape is not perfect market competition and direct at monopsony market. When refer to parctice act of determining price farmer occupy tehe most weak position because farmer just price taker. The performance of rubber not efficient because big margin and not smooth and farmer the most lose out because farmer as price taker.